Economic Assessment of the Euro Area: Autumn 2010 - FITZGERALD, JOHN; BERGIN, ADELE (EUROFRAME - European Forecasting Network, 2010)
The recovery in the world economy from the deepest recession since the 1930s strengthened during the first half of 2010, aided by strong policy measures and restocking. The overall performance of the world economy, however, masks considerable variation in the extent of the economic recovery across different regions. China and the emerging economies have recorded the strongest growth rates while the recovery in the industrialised countries is progressing at a more modest pace as the legacy effects of the crisis weigh on the performance of these economies. On the basis of the latest data available, we expect that the gradual weakening of the recovery seen in recent months will continue into 2011. For 2012, we expect world GDP growth to accelerate slightly as economic conditions gradually improve and economic growth slowly returns to its potential.
PUBLISHED
Europe
Keywords: Economics; Euro